CHILDHOOD OBESITY: EPIDEMIOLOGY, RISK FACTORS, AND EVIDENCE-BASED PREVENTION AND TREATMENT — AN UPDATED NARRATIVE REVIEW (2019–2025) - Helena Szelka; Krystian Czyżykowski; Anna Maria Gęsińska; Bartosz Golis; Paweł Edyko; Alicja Babula; Wiktor Golus; Katarzyna Andrzejewska; Zuzanna Przybyła; Hubert Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
Childhood obesity is a growing global health challenge with serious medical, psychosocial, and economic consequences. Its prevalence has increased substantially over the past decades across both high- and low-income countries, with marked geographic and socioeconomic disparities. This narrative review synthesizes recent evidence (2019–2025) on the epidemiology, risk factors, prevention, and treatment of childhood obesity. Findings indicate that more than one in five children worldwide is overweight or obese, with risk shaped by multiple determinants including ultra-processed food consumption, short sleep, sedentary behaviors, family environment, and genetic predisposition. Preventive strategies at the school and family level show modest effects, whereas structural interventions such as food marketing restrictions and fiscal policies may exert greater population-level impact. Intensive behavioral interventions remain the foundation of treatment, while new pharmacological agents, particularly GLP-1 receptor agonists such as liraglutide and semaglutide, demonstrate unprecedented efficacy but require further long-term evaluation. Bariatric surgery, performed in specialized centers, provides durable weight loss and remission of comorbidities in carefully selected adolescents. Addressing childhood obesity requires integrated, multilevel approaches spanning clinical, familial, educational, and policy domains. Coordinated and sustained action will be essential to reduce the future burden of pediatric obesity and its associated complications.